Tongue of Promise - Owasua 1, Nana Otua (Literamed Publications Nigeria Ltd, 2010)
Jiffa and Vincent have been married for seventeen years when Vincent runs into his first love again. In the turbulence that follows, Jiffa constantly thinks back to the sweet love she had once shared with Mawusi. Were her parents right to have arranged her marriage to her cousin?
Keywords: Fiction; Juvenile Literature